IMPLEMENTASI APPSHEET DAN GOOGLE SHEETS DALAM PERANCANGAN APLIKASI MOBILE UNTUK SALES MKN BERBASIS ANDROID - Aditya Ashadul Ushud, Achmad (Universitas Muhammadiyah Metro, 2025)
This mobile application, built on AppSheet, is designed to facilitate the sales team of PT. Mitra Kerja Nayz in conducting location check-ins and daily reports. The primary goal of its development is to provide an efficient, real-time, and user-friendly attendance and work reporting system. In addition to the check-in feature with automatic location detection and one-tap access, the application includes a daily report feature that enables sales personnel to report sales results and stock levels from visited stores. The user interface is designed based on Android to be simple and accessible for users with varying levels of technological proficiency. The application was developed using the Waterfall methodology, with Google Sheets serving as the database. Implementation results show improved efficiency in both attendance and daily sales activity reporting. This application offers a practical solution to support the mobility, performance tracking, and productivity of the company’s field sales team.